2014
DOI: 10.1016/j.colsurfa.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The significance of lipid peroxidation in cardiovascular disease

Abstract: Background: The metabolic syndrome describes a cluster of cardiovascular risk factors that frequently appear together. Its diagnosis is generally based on several well-recognized indicators in clinical practice, such as abdominal obesity, elevated triglycerides, reduced highdensity lipoprotein, raised blood pressure, and elevated fasting plasma glucose. Today, decisive importance must be attached to the metabolic syndrome since it leads to increased morbidity and mortality, and thus to a decreased life expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The lipid peroxidation detected by Isoprostane level was suggested as one of the key mechanism regarding to effect of air pollution on vascular diseases [ 32 ]. The complex combination of lipid peroxidation markers closely related to change of nano-plaque formation or size [ 33 ]. Hence, that clinical intervention study suggested that markers of lipid peroxidation might serve for monitoring of early diseases progress [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid peroxidation detected by Isoprostane level was suggested as one of the key mechanism regarding to effect of air pollution on vascular diseases [ 32 ]. The complex combination of lipid peroxidation markers closely related to change of nano-plaque formation or size [ 33 ]. Hence, that clinical intervention study suggested that markers of lipid peroxidation might serve for monitoring of early diseases progress [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex combination of lipid peroxidation markers closely related to change of nano-plaque formation or size [ 33 ]. Hence, that clinical intervention study suggested that markers of lipid peroxidation might serve for monitoring of early diseases progress [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For short, the results of biomarker pattern analysis in the blood plasma of the patients shall be summarized as follows: nanoplaque formation was reduced by 14.3% (p < 0.0038) (from 1.0335 ± 0.0515 to 0.8857 ± 0.0185 [1]; p < 0.0077), nanoplaque size by 23.4% (p < 0.0010) (from 1.0730 ± 0.0741 to 0.8216 ± 0.0588 [1]; p < 0.0004), oxLDL/LDL by 21.0% (p < 0.002) (from 65.1 ± 3.0 to 50.7 ± 2.4 U/g; p < 0.0008), 8-iso-PGF 2a by 39.8% (p < 0.0084) (from 24.9 ± 4.6 to 15.0 ± 2.0 nmol/L; p < 0.0027), MPO by 29.6% (p < 0.0137) (from 60.4 ± 7.8 to 41.1 ± 7.7 ng/mL; p < 0.0118), IL-6 by 12.9% (p < 0.0407) (from 3.0 ± 0.5 to 2.6 ± 0.5 pg/mL; p < 0.0337), Lp(a) by 26.3% (p < 0.001) (from 50.8 ± 7.3 to 39.5 ± 6.3 mg/dL; p < 0.0005), MMP-9 by 32.9% (p < 0.042) (from 353.0 ± 60.5 to 228.4 ± 61.2 ng/mL; p < 0.0420), whereas SOD was augmented by 17.7% (p < 0.0095) (from 126.2 ± 9.0 to 146.2 ± 11.4 U/mL; p < 0.0095), GPx by 11.6% (p < 0.001) (from 6.0 ± 0.2 to 6.7 ± 0.2 U/ mL; p < 0.0005), cAMP by 43.5% (p < 0.001) (from 40.3 ± 3.8 to 54.5 ± 3.4 nmol/L; p < 0.0002), and cGMP by 32.9% (p < 0.001) (from 8.5 ± 0.5 to 10.9 ± 0.5 nmol/L; p < 0.0016) [2,4,5,7]. Detailed data for baseline values of body mass index, glucose, insulin, triglycerides (important potential confounders), as well as for lowering in hs-CRP and HOMA-IR are presented in Table 1.…”
Section: Resultsmentioning
confidence: 90%
“…Since we had observed a decrease both in hs-CRP and HOMA-IR as well as in nanoplaque formation and size, biomarkers of oxidative stress, plaque formation, stability and progression, and inflammation in a clinical pilot study in MS patients treated with Ginkgo biloba, we revisited these laboratory parameters [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, its four double bonds render it more susceptible to oxidation (Gardner 1989) and its 5-trans and 8-trans isomers are related to the endogenous radical-based cis-trans isomerization (Folch, Lees et al 1957, Ferreri, Samadi et al 2004. Taking into account also the close relationship between oxidative stress and lipid peroxidation with various pathological conditions including cancer, cardiovascular disease, and diabetes (Birben, Sahiner et al 2012, Siegel, Ermilov et al 2014, investigating the role of cis-trans arachidonic acid isomerization on the membrane physicochemical properties could provide additional useful information on the role of stress root conditions in health and disease.…”
Section: Introductionmentioning
confidence: 99%